Environmental, Social, Governance - Sustainability Disclosure Using International Financial Reporting Sustainability Standards S1 in Southeast Asian Companies: A Preliminary Assessment - Pratama, Arie; Jaenudin, Edi; Anas, Syaiful (International Journal of Energy Economics and Policy, 2022)
This research aims to analyse the gaps in a company’s annual reports related to the disclosure requirements in the International Financial Reporting Sustainability Standard (IFRS) S1 and compare them to other companies and business sectors in Southeast Asia. This research analyses 224 companies listed on Environmental, Social and Governance (ESG)-related indexes in Thailand, Singapore, Indonesia and Malaysia. The assessment was done using a disclosure quality matrix consisting of four criteria: (1) Governance (GOV); (2) Strategy (STR); (3) Risk (RSK); and (4) Target and Metrics (MTR). The results of the study show that: (1) Based on the extent and quality of the disclosures, almost all companies fully disclosed GOV, STR and RSK but not MTR; (2) In general, there is a difference between the extent and quality of the disclosures among countries and industries; (3) From the four clusters formed, 94 out of 224 companies classified in the best clusters, while only 12 out of 224 companies classified in the worst clusters. This research implies that there is still much to be done to improve sustainability reporting, including an effort to reduce disparities in the quality and extent of disclosure between countries and business sectors.